Designing a new wood-composite material made from logging waste - Pinchevska, Olena; Lakyda, Yurii; Baranova, Olha; Biletskyi, Mykhailo; Holovach, Valentin; Oliinyk, Rostyslav; Yeroshenko, Andrii (Eastern-European Journal of Enterprise Technologies, 2020)
This study has confirmed the possibilities of using logging waste for the production of wood-composite material. The raw material for its manufacturing is the wood weaving made by flattening branches. An experimental study into the physical, mechanical, and technological properties of the wood-composite material made from the poplar branches has made it possible to determine its rational structure and the type of a binder. It has been established that ensuring the flat shape of the material requires that it should be formed of three mutually perpendicular layers. It is advisable to use urea formaldehyde resin as a binder for plates that are not exposed to the impact and static loads and are used indoors. When the material is to be applied under conditions of elevated loads and in places with high humidity, phenol-formaldehyde resin should be used. The rational pressing mode parameters have been defined: temperature, t=180 °C; pressure, p=8 MPa; holding time, τ=7 min., at which one can achieve a minimum deformation of plates after pressing. It has been proven that under these schedule parameters the holding time for the new wood-composite material to achieve the shape stabilization is also minimal; it is seven days. It has been determined that the new wood-composite material possesses the physical and mechanical properties similar to those of the OSB panels